2004
DOI: 10.1081/prg-120028291
|View full text |Cite
|
Sign up to set email alerts
|

Do Commonly Used Oral Antihypertensives Alter Fetal or Neonatal Heart Rate Characteristics? A Systematic Review

Abstract: Available data are inadequate to conclude whether oral methyldopa, labetalol, nifedipine, or hydralazine adversely affect fetal or neonatal heart rate and pattern. Until definitive data are available, FHR changes cannot be reliably attributed to drug effect, but may be due to progression of the underlying maternal or placental disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 41 publications
(17 reference statements)
1
20
0
1
Order By: Relevance
“…The perinatal literature suggests that abnormal fetal monitoring of various types may identify increased fetal risk. Abnormalities in the NST should not be ascribed to antihypertensive therapy [90]. Computerized NST improves perinatal outcomes compared with visual interpretation in high risk pregnancies [91].…”
Section: The Adverse Conditionsmentioning
confidence: 99%
“…The perinatal literature suggests that abnormal fetal monitoring of various types may identify increased fetal risk. Abnormalities in the NST should not be ascribed to antihypertensive therapy [90]. Computerized NST improves perinatal outcomes compared with visual interpretation in high risk pregnancies [91].…”
Section: The Adverse Conditionsmentioning
confidence: 99%
“…Oral ␤-blockade had been associated with nonclinically significant neonatal bradycardia, 14,47 although in a systematic review of trials, labetalol does not (along with oral methyldopa, nifedipine, or hydralazine) seem to cause neonatal heart rate effects. 48 Parenteral therapy has been found to increase the risk of neonatal bradycardia, requiring intervention in 1 of 6 newborns. 14 Further reassurance is derived from a 1-year postpartum follow-up study, which showed normal development of infants exposed to atenolol in utero.…”
Section: Peripherally Acting Adrenergicmentioning
confidence: 99%
“…However, adverse effects on the fetus such as intrauterine growth restriction (IUGR), cardiorespiratory depression, bradycardia, hypoglycemia, and hypothermia have been observed when betablockers are used throughout pregnancy [35,36]. A recent systematic review, however, found that there was insufficient evidence to draw conclusions about the effects of betablockers on perinatal outcomes [37].…”
Section: Betablockersmentioning
confidence: 95%